2010
DOI: 10.1051/0004-6361/201014678
|View full text |Cite
|
Sign up to set email alerts
|

Herschel-SPIRE observations of the Polaris flare: Structure of the diffuse interstellar medium at the sub-parsec scale

Abstract: We present a power spectrum analysis of the Herschel-SPIRE observations of the Polaris flare, a high Galactic latitude cirrus cloud midway between the diffuse and molecular phases. The SPIRE images of the Polaris flare reveal for the first time the structure of the diffuse interstellar medium down to 0.01 parsec over a 10 square degrees region. These exceptional observations highlight the highly filamentary and clumpy structure of the interstellar medium even in diffuse regions of the map. The power spectrum a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
2
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(89 citation statements)
references
References 10 publications
6
79
2
2
Order By: Relevance
“…(A color version of this figure is available in the online journal.) recently, studies of various fields using BLAST and SPIRE data have found a much wider range of the index, e.g., α c ∼ −2.4 (Bracco et al 2011), −2.6 , −2.8 Miville-Deschênes et al 2010), −2.9 , and even ranging from −2.5 to −3.6, depending on the field (Miville-Deschênes et al 2007). Thus, rather than assume a power law with α = −3 (e.g., Viero et al 2009), we proceed by treating each field independently.…”
Section: Galactic Cirrusmentioning
confidence: 99%
“…(A color version of this figure is available in the online journal.) recently, studies of various fields using BLAST and SPIRE data have found a much wider range of the index, e.g., α c ∼ −2.4 (Bracco et al 2011), −2.6 , −2.8 Miville-Deschênes et al 2010), −2.9 , and even ranging from −2.5 to −3.6, depending on the field (Miville-Deschênes et al 2007). Thus, rather than assume a power law with α = −3 (e.g., Viero et al 2009), we proceed by treating each field independently.…”
Section: Galactic Cirrusmentioning
confidence: 99%
“…This characteristic can be examined by calculating the spatial power spectra of the cirrus distribution taken from the AKARI diffuse all sky survey, as the cirrus power spectra can be well represented by power-law spectra (see e.g., Miville-Deschênes et al, 2010;Martin et al, 2010).…”
Section: Spatial Power Spectramentioning
confidence: 99%
“…The uncertainty in submm colour G is estimated by taking the rms of the ratio involving S(λ)/I(100) once the offset S 0 is removed from each of the maps, while the uncertainty in S 0 comes from the rms of the difference involving S(λ) − G × I(100), with the best-fitting values for submm colour used in the computation. As described in Miville-Deschênes et al (2010), these rms values reflect the overall uncertainties more accurately than if one were to simply use the statistics associated with the linear fit to the relation between S(λ) and I(100). Those have uncertainties that are at least a factor of 10 smaller than the errors quoted above.…”
Section: Zero-level In Spire Mapsmentioning
confidence: 99%
“…Some of these clouds may be on the verge of gravitational collapse leading to the formation of a new star (Olmi et al 2010;Sadavoy, Di Francesco & Johnstone 2010;Ward-Thompson et al 2010). At large angular scales, dust is a key tracer of the large-scale physical processes occurring in the diffuse ISM (Miville-Deschênes et al 2010). Dust emission is also related to the density structure of diffuse clouds and could potentially provide a way to study the projected density distribution within the Galactic cirrus.…”
Section: Introductionmentioning
confidence: 99%